Sensitivity analysis for a problem of optimal structure design - Nhu, Ngo Huong (Vietnam Journal of Mechanics, 1994)
On the basis of theory of structure sensitivity analysis, the gradient – projection method and the finite element method, a detailed and effective algorithm of determination of the sensitivity-vector for the optimal structure design problem is proposed. Numerical results illustrating the program corresponding to this algorithm have been given for some plane frames.